Liquidity Trap: the Brazilian version - Ferrari Filho, Fernando; Milan, Marcelo (Brazilian Keynesian Review, 2019)
The goal of this paper is to provide an interpretation about the sky-high real interest rates in Brazil. We use Keynes’ argument regarding liquidity trap to identify the forces trapping interest rates, but in Brazil they are trapped at very high levels instead of at the zero-lower bound discussed in Keynes’s General Theory. Rentiers, in Brazil, influence the Brazilian Central Bank to obtain very liquid assets in the form of Financial Treasury Bills (LFTs) while keeping high interest earnings. In this case expansionary fiscal policies will have a limited impact on output, given the resulting high debt levels and debt service, but will imply significant income transfers to the rentiers. This means that aggregate demand and income will be less sensitive to fiscal stimuli, but the distribution of income will be biased toward the rentiers.